Vertical Stability Analysis of Permanent-magnet EDS System with Permanent Magnets and Electromagnets Hybrid Halbach Array. Issue 24 (2019) - Cheng, Luo; Kun-lun, Zhang
Abstract: This paper studies the vertical stability of permanent-magnet EDS system with permanent magnets and electromagnets hybrid Halbach array, which can realize active damping control of permanent-magnet EDS system by winding active normal conductor coils on permanent magnets. Firstly, the vertical dynamic stability of permanent magnets EDS system with permanent magnets Halbach array is analyzed. Research result shows that this system will cause sustained oscillation under the action of external disturbing force. So the permanent magnets and electromagnets hybrid Halbach array is proposed to achieve the system active damping control. Secondly, the fuzzy self-tuning PID controller is designed to meet the vertical dynamic performance. Finally the Simulink is used to simulate the levitation dynamic stability under the disturbances of external disturbing force and rail step disturbance. The simulation results show that the system can quickly and stably levitate at rated gap 30 mm. And when the external disturbing forces are ±800 N, the stable currents of coils are 42.16 A and -43.26 A, respectively, proving that the permanent-magnet EDS system with permanent magnets and electromagnets hybrid Halbach array can realize vertical dynamic stability.